Answer:
x=0
Step-by-step explanation:
ima break it apart so it is easier to understand, going from left to right.
15(x-3)/5 you will distribute the 15 to the x and the -3
15x-45/5 you will divide 5 to both the 15x and the 45
3x-9 it will now be combined with the right side
now on the right side:
3(2x-3) you will distribute the 3 to the 2x and -3
6x-9 will now be combined with the left side
combining the left and right.
3x-9=6x-9 combine both 'x' es and constants
3x-6x=9-9 solve
-3x=0 divide
-3x=0 /-3 (all of it will be divided by 3 cuz what you do to one side, you gotta do to the other)
x=0
without distributive property
15(x-3)/5=3(2x-3) remove the parenthesis from the left side
3(x-3)=3(2x-3) distribute the 3 through the parenthesis on both sides
3x-9=6x-9 the rest is the same as in the combined section up above.
i hope this helps